Concentrations of MDPV in rat striatum correlate with the psychostimulant effect. (November 2015) - Novellas, Judith; López-Arnau, Raúl; Carbó, Marcel·li; Pubill, David; Camarasa, Jorge; Escubedo, Elena
3, 4-methylenedioxypyrovalerone or MDPV is a synthetic cathinone with psychostimulant properties more potent than cocaine. We quantified this drug in the striatum after subcutaneous administration to rats. MDPV reached the brain around 5 min after its administration and peaked at 20–25 min later. The elimination half-life in the striatum (61 min) correlates with the decrease in the psychostimulant effect after 60 min. Around 11% of the administered dose reached the striatum and, considering a homogeneous brain distribution, we determined that around 86% of the plasma MDPV is distributed to the brain. MDPV induced a dose-dependent increase in locomotor activity, rearing behaviour and stereotypies, all prevented by haloperidol. A plot of locomotor activity or stereotypies versus MDPV striatal concentrations over time showed a direct relationship between factors. No free MDPV metabolites were detected in plasma, at any time, but hydrolysis with glucuronidase allowed us to identify mainly three metabolites, one of them for the first time in rat plasma. The present results contribute to evidence that MDPV induces hyperlocomotion mainly through a dopamine-dependent mechanism. Good correlation between behavioural effects and striatal levels of MDPV leads us to conclude that its psychostimulant effect is mainly due to a striatal distribution of the substance. The present research provides useful information on the pharmacokinetics of MDPV, and can help design new experiments with kinetics data as well as provide a better understanding of the effects of MDPV in humans and its potential interactions.